Pendekatan Pembelajaran Kreatif untuk Meningkatkan Keterampilan Siswa - Kasmir, Elly; Usman, Syahruddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
Creative learning is an approach that emphasizes the development of students’ critical thinking, imagination, and innovation skills. This article discusses the concept of creative learning, its implementation strategies, and its impact on improving students’ skills. A literature review method is used to examine recent research and theories on creative learning. The results indicate that learning strategies that encourage experimentation, discussion, and creative projects can significantly enhance students’ understanding, motivation, and skills. Implementing creative learning is key to producing adaptive and innovative generations.